Histidine hypophosphite inorganic-organic hybrid nonlinear optical crystal and preparation and application thereof

By combining organic chiral motifs and inorganic tetrahedral anions to form histidine hypophosphate inorganic-organic hybrid nonlinear optical crystals, the problem of existing materials being difficult to achieve strong frequency multiplication response and wide band gap at the same time, achieving high efficiency The laser frequency conversion and photoelectric modulation broadens the application field and improves the thermal stability of the material.

CN119320993AActive Publication Date: 2025-01-17TONGJI UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411120246.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-15
Publication Date
2025-01-17
Estimated Expiration
2044-08-15

AI Technical Summary

Technical Problem

Existing ultraviolet inorganic-organic hybrid nonlinear optical materials are difficult to achieve strong frequency multiplication response and wide band gap optical performance at the same time, limiting their applications in the fields of laser frequency conversion, photoelectric modulation and holographic storage of laser signals.

Method used

By combining organic chiral motifs (L-C6H10N3O2 or D-C6H10N3O2) and inorganic tetrahedral anion (H2PO2-), histidine hypophosphate inorganic-organic hybrid nonlinear optical crystals are formed, and prepared by the slow volatilization method of aqueous solution. Crystals with large band gaps and strong frequency multiplication responses are formed.

Benefits of technology

A crystal with a large frequency doubling effect and phase matching under 1064nm laser irradiation is achieved. The ultraviolet absorption cut-off edge is 233nm or 234nm, and the optical band gap reaches 5.32eV or 5.30eV, which broadens the application prospects of materials and improves heat. The decomposition temperature is 203°C.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320993A_ABST
    Figure CN119320993A_ABST
Patent Text Reader

Abstract

The invention relates to a histidine hypophosphite inorganic-organic hybrid nonlinear optical crystal as well as preparation and application thereof, the chemical formula of the optical crystal is A (H2PO2), and A is L-C6H10N3O2 or D-C6H10N3O2; the crystal belongs to a monoclinic system, the space group is P21, the cell parameters are # imgabs0 # imgabs1 #, alpha = gamma = 90 degrees, beta = 99.0-99.4 degrees, and Z = 2. The birefringence of the crystal (L-C6H10N3O2) (H2PO2) and the birefringence of the crystal (D-C6H10N3O2) (H2PO2) at the position of 546 nm are 0.084 and 0.058, the powder SHG coefficient of the crystal (L-C6H10N3O2) (H2PO2) under the irradiation of 1064 nm laser is 1 or 2 times that of KH2PO4 (KDP), and phase matching can be achieved under the irradiation of 1064 nm laser. Besides, the ultraviolet absorption cut-off edges of the crystal material are 233 nm and 234 nm, the corresponding optical band gaps of the crystal material reach 5.32 eV and 5.30 eV respectively, and the crystal material has wide application prospects in the field of ultraviolet laser.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nonlinear optical crystals and relates to a histidine hypophosphite inorganic-organic hybrid nonlinear optical crystal and a preparation method and application thereof. Background Art

[0002] Second-order nonlinear optical crystals are optoelectronic functional materials widely used in the field of lasers. They have important application value in laser frequency conversion, optoelectronic modulation, holographic storage of laser signals, laser communications, etc. At present, the second-order nonlinear optical phosphate materials that have been put into practical use include potassium dihydrogen phosphate (KH2PO4), potassium titanyl phosphate (KTiOPO4), L-arginine phosphate ((H2N)2CNH(CH2)3CH(NH3)COO·H2PO4·H2O), etc. Among them, inorganic-organic hybrid nonlinear optical materials used in the ultraviolet band are often constrained in practical applications due to their inherent defects. The above research and applications have put forward more and higher requirements for the physical and chemical properties of ultraviolet inorganic-organic hybrid nonlinear optical materials, and also promoted the rapid development of inorganic-organic hybrid nonlinear optical materials. In addition to having a non-centrosymmetric structure, an excellent ultraviolet inorganic-organic hybrid nonlinear optical crystal material also needs to show strong frequency response, wide band gap, appropriate birefringence and stable physical and chemical properties. However, wide bandgap and strong frequency doubling, as two opposing key optical properties, are often difficult to achieve simultaneously in a nonlinear optical crystal.

[0003] In recent years, it has become an effective strategy to construct materials with strong frequency doubling effect by combining two types of functional units (such as organic chiral units and inorganic tetrahedral units). Among them, organic chiral units have the characteristics of strong frequency doubling effect and high optical anisotropy, while inorganic tetrahedral units have the characteristics of wide transmission band and thermal stability. Through the secondary bond between the units, it is expected to obtain inorganic-organic hybrid nonlinear optical crystal materials that take into account all their characteristics. Currently, the only commercial organic-inorganic hybrid nonlinear optical L-arginine phosphate (LAP) crystal was first explored and grown by Jiang Minhua's team at Shandong University in the 1980s. However, its thermal decomposition temperature is 112°C, which limits its application in high temperature areas. In addition, there is also room for further expansion in other nonlinear optical properties. Summary of the invention

[0004] The purpose of the present invention is to provide a histidine hypophosphite inorganic-organic hybrid nonlinear optical crystal and its preparation and application, by combining an organic chiral unit (L-C6H 10 N3O2) + or (D-C6H 10 N3O2) +and inorganic tetrahedral anions (H2PO2) - , an inorganic-organic hybrid nonlinear optical crystal material with both a large band gap and a strong double-frequency response is obtained.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] In one aspect, the present invention provides a histidine hypophosphite inorganic-organic hybrid nonlinear optical crystal, characterized in that its chemical formula is A(H2PO2), wherein A is L-C6H 10 N3O2 or D-C6H 10 N3O2(please).

[0007] Furthermore, the optical crystal belongs to the monoclinic system, the space group is P21, and the unit cell parameters are α=γ=90°, β=99.0~99.4°, Z=2.

[0008] Furthermore, the chemical formula of the crystal is (L-C6H 10 N3O2)(H2PO2) belongs to the monoclinic system, the space group is P21, and the unit cell parameters are α=γ=90°,β=99.0~99.4,Z=2. Further preferably, the unit cell parameters are α=γ=90°,β=99.05~99.35°,Z=2. Further preferably, the unit cell parameters are α=γ=90°,β=99.059~99.345,Z=2. More preferably, the unit cell parameters are α=γ=90°, β=99.185(2)°, Z=2.

[0009] Each asymmetric unit contains a chiral L-histidine cation, a hypophosphite tetrahedral anion and two hydrogen bonds (N2-H2···O4 and N3-H3B···O3) (e.g. Figure 1 a). The smallest asymmetric units are connected by hydrogen bonds (C1-H 1A ···O3 and N3-H 3C ···O4) forms a one-dimensional (1D) infinite spiral chain along the coordinate axis b (such as Figure 1 b). Adjacent helical chains form a two-dimensional wavy layered structure in plane ab through hydrogen bonds (N1-H1···O1) Figure 1 c). This final 3D framework is composed of 2D layers through hydrogen bonds (N3-H 3A ···O3 and C5-H5···O2) stacked together ( Figure 1 d).

[0010] The inorganic-organic hybrid (L-C6H 10 The ultraviolet absorption cutoff wavelength of the (N3O2) (H2PO2) crystal is 233-237 nm. Preferably, the ultraviolet absorption cutoff wavelength of the inorganic-organic hybrid nonlinear optical crystal is 233 nm.

[0011] Furthermore, the chemical formula of the crystal is (D-C6H 10 N3O2)(H2PO2) belongs to the monoclinic system, the space group is P21, and the unit cell parameters are α=γ=90°,β=99.0~99.4°,Z=2. Further preferably, the unit cell parameters are α=γ=90°,β=99.05~99.35°,Z=2. Further preferably, the unit cell parameters are α=γ=90°,β=99.059~99.345°,Z=2. More preferably, the unit cell parameters are α=γ=90°, β=99.193(2)°, Z=2.

[0012] Each asymmetric unit contains a chiral D-histidine cation, a hypophosphite tetrahedral anion and two hydrogen bonds (N2-H2···O4 and N3-H3B···O3) (e.g. Fig. 9 a). The smallest asymmetric units are connected by hydrogen bonds (C1-H 1A ···O3 and N3-H 3C ···O4) forms a one-dimensional (1D) infinite spiral chain along the coordinate axis b (such as Fig. 9 b). Adjacent helical chains form a two-dimensional wavy layered structure in plane ab through hydrogen bonds (N1-H1···O1) Fig. 9 c). This final 3D framework is composed of 2D layers through hydrogen bonds (N3-H 3A ···O3 and C5-H5···O2) stacked together ( Fig. 9 d).

[0013] The inorganic-organic hybrid (D-C6H 10 The ultraviolet absorption cutoff wavelength of the (N3O2) (H2PO2) crystal is 234-238 nm. Preferably, the ultraviolet absorption cutoff wavelength of the inorganic-organic hybrid nonlinear optical crystal is 234 nm.

[0014] In a second aspect, the present invention provides a method for preparing a histidine hypophosphite inorganic-organic hybrid nonlinear optical crystal, comprising mixing raw materials containing a histidine source, hypophosphorous acid and water, placing the mixture in an open evaporation container, volatilizing and crystallizing the mixture to obtain a target product.

[0015] Furthermore, the histidine source is L-histidine or D-histidine.

[0016] Furthermore, the molar ratio of the histidine source, hypophosphorous acid and water is 5:5-10:500-1500, preferably, the molar ratio of the histidine source, hypophosphorous acid and water is 5:(5-10):500-750.

[0017] Furthermore, the temperature of volatilization and crystallization is 15 to 45°C, preferably 25 to 35°C.

[0018] Furthermore, the volatilization and crystallization time is not less than 14 days, preferably 14 to 21 days.

[0019] Furthermore, after the crystallization is completed, the temperature is lowered to room temperature at a cooling rate of 0.5° C. / h to 10° C. / h, preferably 0.5 to 3° C. / h.

[0020] In a third aspect, the present invention provides an application of a histidine hypophosphite inorganic-organic hybrid nonlinear optical crystal in a laser frequency converter.

[0021] Furthermore, the laser frequency converter is used to output 532nm green light under 1064nm laser irradiation.

[0022] Specifically, (L-C6H 10 Application of N3O2)(H2PO2) crystal as nonlinear optical crystal material. It outputs strong 532nm green light under 1064nm laser irradiation. Its powder SHG coefficient is 1 times that of KH2PO4(KDP), and phase matching can be achieved.

[0023] (D-C6H 10 N3O2)(H2PO2) crystal is used as a nonlinear optical crystal material. It outputs a strong 532nm green light under 1064nm laser irradiation. Its powder SHG coefficient is twice that of KH2PO4 (KDP) and can achieve phase matching.

[0024] Compared with the prior art, the present invention has the following advantages:

[0025] (1) This application provides a new inorganic-organic hybrid nonlinear optical crystal (L-C6H 10N3O2)(H2PO2), this crystal material has a large frequency doubling effect, which is about 1 times the frequency doubling intensity of KH2PO4 crystal under 1064nm laser irradiation, and can achieve phase matching. In addition, the ultraviolet absorption cutoff edge of this crystal material is 233nm, and the optical band gap reaches 5.32eV. This crystal material achieves an effective balance between strong frequency doubling response and wide band gap, and has broad application prospects in the fields of ultraviolet laser frequency conversion, optoelectronic modulation, and laser signal holographic storage.

[0026] (2) The present application also provides the inorganic-organic hybrid nonlinear optical crystal material (L-C6H 10 The preparation method of N3O2)(H2PO2) adopts the method of slow volatilization of aqueous solution, takes 50% hypophosphorous acid aqueous solution as raw material and reaction solvent at 15-45°C, and obtains high-purity and high-crystallinity inorganic-organic hybrid (L-C6H 10 N3O2)(H2PO2) nonlinear optical crystal material.

[0027] (3) This application provides a new inorganic-organic hybrid nonlinear optical crystal (D-C6H 10 N3O2)(H2PO2), this crystal material has a large frequency doubling effect, which is about twice the frequency doubling intensity of KH2PO4 crystal under 1064nm laser irradiation, and can achieve phase matching. In addition, the ultraviolet absorption cutoff edge of this crystal material is 234nm, and the optical band gap reaches 5.30eV. This crystal material achieves an effective balance between strong frequency doubling response and wide band gap, and has broad application prospects in the fields of ultraviolet laser frequency conversion, optoelectronic modulation, and laser signal holographic storage.

[0028] (4) The present application also provides the inorganic-organic hybrid nonlinear optical crystal (D-C6H 10 The preparation method of N3O2)(H2PO2) adopts the method of slow volatilization of aqueous solution, takes 50% hypophosphorous acid aqueous solution as raw material and reaction solvent at 15-45°C, and reacts with histidine through efficient acid-base neutralization reaction to obtain high-purity and high-crystallinity inorganic-organic hybrid (D-C6H 10 N3O2)(H2PO2) nonlinear optical crystal material.

[0029] (5) The thermal decomposition temperature of the histidine hypophosphite inorganic-organic hybrid nonlinear optical crystal of the present invention can reach 203° C., which greatly improves the stability of the inorganic-organic hybrid nonlinear optical crystal. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Yes (L-C6H 10Schematic diagram of the crystal structure of N3O2)(H2PO2); (a) asymmetric unit; (b) one-dimensional chain structure; (c) two-dimensional layer structure; (d) three-dimensional structure;

[0031] Figure 2 The X-ray diffraction pattern of sample 1-1# obtained by fitting the crystal structure analyzed by single crystal X-ray diffraction is compared with the pattern obtained by X-ray diffraction test after sample 1-1# is ground into powder;

[0032] Figure 3 is the UV transmission spectrum of sample 1-1#;

[0033] Figure 4 is the infrared vibration spectrum of sample 1-1#;

[0034] Figure 5 This is the thermogravimetric analysis spectrum of sample 1-1#;

[0035] Figure 6 It is the second harmonic signal diagram of sample 1-1# and standard KDP sample with sample size ranging from 105 to 150 μm;

[0036] Figure 7 This is the second harmonic phase matching diagram of sample 1-1# in the 1064nm band;

[0037] Figure 8 is a graph of birefringence test, where (a) (L-C6H 10 N3O2)(H2PO2) without extinction; (b)(L-C6H 10 N3O2)(H2PO2) complete extinction; (c)(L-C6H 10 N3O2)(H2PO2) crystal thickness;

[0038] Fig. 9 Yes (D-C6H 10 Schematic diagram of the crystal structure of N3O2)(H2PO2); (a) asymmetric unit; (b) one-dimensional chain structure; (c) two-dimensional layer structure; (d) three-dimensional structure;

[0039] Fig.10 The X-ray diffraction pattern of sample 2-1# obtained by fitting the crystal structure analyzed by single crystal X-ray diffraction is compared with the pattern obtained by X-ray diffraction test after sample 2-1# is ground into powder;

[0040] Fig.11 is the UV transmission spectrum of sample 2-1#;

[0041] Fig.12 is the infrared vibration spectrum of sample 2-1#;

[0042] Fig.13 This is the thermogravimetric analysis spectrum of sample 2-1#;

[0043] Fig.14 It is the second harmonic signal diagram of sample 2-1# and standard KDP sample with sample size ranging from 105 to 150 μm;

[0044] Fig.15 This is the second harmonic phase matching diagram of sample 2-1# in the 1064nm band;

[0045] Fig.16 is a graph of the birefringence test, where (a) (D-C6H 10 N3O2)(H2PO2) without extinction; (b)(D-C6H 10 N3O2)(H2PO2) complete extinction; (c)(D-C6H 10 N3O2)(H2PO2) crystal thickness. DETAILED DESCRIPTION

[0046] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0047] Example 1

[0048] Preparation of samples 1# to 8#

[0049] The histidine source, hypophosphorous acid (added in the form of a solution with a concentration of 50 wt%) and water were mixed in a certain proportion to form a raw material, placed in an evaporating dish, heated to the crystallization temperature, kept constant for a period of time, and then the system temperature was slowly lowered to room temperature at a certain rate, filtered and washed, and a colorless block (L-C6H 10 N3O2)(H2PO2) crystals.

[0050] The relationship between the type and ratio of raw materials in the initial mixture, crystallization temperature, crystallization time and sample number is shown in Table 1.

[0051] Table 1 Correspondence between samples, raw materials and synthesis conditions

[0052]

[0053] Crystal structure analysis of samples 1# to 8#

[0054] The structures of samples 1-1# to 1-8# were analyzed using single crystal X-ray diffraction and powder X-ray diffraction methods.

[0055] The single crystal X-ray diffraction was performed on a D8 VENTURE CMOS X-ray single crystal diffractometer from Bruker, Germany. The data collection temperature was 293K, and the diffraction light source was graphite monochromatized Mo-Kα rays. The scanning mode was ω; the data were processed for absorption correction using the Multi-Scan method. The structure analysis was completed using the SHELXTL-2017 program package; the positions of heavy atoms were determined using the direct method, and the coordinates of the remaining atoms were obtained using the difference Fourier synthesis method; the F-based 2 The full-matrix least-squares method was used to refine the coordinates of all atoms and the anisotropic thermal parameters.

[0056] Powder X-ray diffraction was carried out on a Bruker D8 X-ray powder diffractometer from Bruker, Germany. The test conditions were a fixed target monochromatic light source Cu-Kα, a wavelength The voltage and current are 40 kV / 20 A, the slits DivSlit / RecSlit / SctSlit are 2.00 deg / 0.3 mm / 2.00 deg respectively, the scanning range is 5 to 70°, and the scanning step is 0.02°.

[0057] Among them, the single crystal X-ray diffraction results show that samples 1-1# to 1-8# have the same chemical formula and crystal structure, and the chemical formula is (L-C6H 10 N3O2)(H2PO2) belongs to the monoclinic system, the space group is P21, and the unit cell parameters are α=γ=90°, β=99.059~99.345°, Z=2.

[0058] Take sample 1-1# as a typical representative, its crystal structure data is α=γ=90°,β=99.185(2)°,Z=2,the unit cell volume is Its crystal structure is Figure 1 shown.

[0059] Take sample 1-1# as a typical example. Figure 2 As shown, according to the crystal structure analyzed by single crystal X-ray diffraction, the fitted X-ray diffraction pattern is consistent with the pattern obtained by X-ray diffraction test after sample 1-1# is ground into powder, and the peak position and peak intensity are consistent, indicating that the obtained samples are of high purity.

[0060] UV transmittance spectrum test

[0061] The UV transmission spectrum test of sample 1-1# was conducted on a Carry 5000 UV-visible-near infrared spectrophotometer produced by Agilent Technologies, Inc., USA. Figure 3 As shown by Figure 3It can be seen that the ultraviolet absorption cutoff edge of the compound is 233nm and the optical band gap is 5.32eV.

[0062] Infrared spectrum test

[0063] The infrared spectrum test of sample 1-1# was conducted on a Nicolet iS10 Fourier infrared spectrometer from Thermo Fisher Scientific Inc., USA. The results are as follows Figure 4 As shown by Figure 4 The group characteristic peaks of the compound can be seen, further confirming the accuracy of the crystal structure.

[0064] Thermogravimetric testing

[0065] Thermogravimetric test of sample 1-1# was conducted on TGA / DSC1 / 1100SF thermogravimetric analyzer of Mettler-Toledo International Trading (Shanghai) Co., Ltd. The results are shown in Figure 5 As shown, the compound is stable up to 203°C.

[0066] Frequency doubling test experiment and results

[0067] The frequency doubling test experiment of sample 1-1# is as follows: a Q-switched Nd:YAG solid laser is used to generate a wavelength of 1064nm as the fundamental frequency light to irradiate the tested crystal powder, a photomultiplier tube is used to detect the generated second harmonic, and an oscilloscope is used to display the harmonic intensity. The crystal sample and the standard sample KDP crystal are ground separately, and crystals of different particle sizes are sieved out with a standard sieve, and the particle size ranges are less than 50-74, 74-105, 105-150, 150-200, and 200-280μm, respectively. Observe the change trend of the frequency doubling signal with the particle size to determine whether it can achieve phase matching. Under the same test conditions, the second harmonic intensity generated by the sample and the reference crystal KDP under 1064nm wavelength laser irradiation is compared to obtain the relative size of the sample frequency doubling effect.

[0068] The test results show that the compound (L-C6H 10 N3O2)(H2PO2) crystal has a large frequency doubling effect. Under 1064nm wavelength laser irradiation, the frequency doubling signal intensity is 1 times that of KDP crystal (such as Figure 6 ).like Figure 7 As shown, the crystal material can achieve phase matching in the 1064nm laser band.

[0069] Birefringence experiment and results

[0070] The birefringence test experiment of sample 1-1# is as follows:

[0071] (L-C6H 10The birefringence of N3O2)(H2PO2) was evaluated using a ZEISS Axio Scope 5 polarizing microscope equipped with a Berek compensator under a 546 nm light source. e -N o |×T=Δn×T to determine the birefringence, the optical path difference is R, the measured birefringence is Δn, and the crystal thickness is T.

[0072] The test results show that Figure 8 a, (L-C6H 10 N3O2)(H2PO2) is not extinguished. Figure 8 b, (L-C6H 10 N3O2)(H2PO2) is completely extinguished, and its optical path difference is 1.93μm. (L-C6H 10 The crystal thickness of N3O2)(H2PO2 is 23.016μm( Figure 8 c). According to the formula R = Δn × T, (L-C6H 10 The birefringence of N3O2)(H2PO2) is 0.084.

[0073] Example 2

[0074] Preparation of samples 1# to 8#

[0075] The histidine source, hypophosphorous acid (added in the form of a solution with a concentration of 50 wt%) and water were mixed in a certain proportion to form a raw material, placed in an evaporating dish, heated to the crystallization temperature, kept constant for a period of time, and then the system temperature was slowly lowered to room temperature at a certain rate, filtered and washed, and a colorless block (D-C6H 10 N3O2)(H2PO2) crystals.

[0076] The relationship between the type and ratio of raw materials in the initial mixture, crystallization temperature, crystallization time and sample number is shown in Table 2.

[0077] Table 2 Correspondence between samples and raw materials and synthesis conditions

[0078]

[0079]

[0080] Crystal structure analysis of samples 1# to 8#

[0081] The structures of samples 2-1# to 2-8# were analyzed using single crystal X-ray diffraction and powder X-ray diffraction methods.

[0082] The single crystal X-ray diffraction was performed on a D8 VENTURE CMOS X-ray single crystal diffractometer from Bruker, Germany. The data collection temperature was 293K, and the diffraction light source was graphite monochromatized Mo-Kα rays. The scanning mode was ω; the data were processed for absorption correction using the Multi-Scan method. The structure analysis was completed using the SHELXTL-2017 program package; the positions of heavy atoms were determined using the direct method, and the coordinates of the remaining atoms were obtained using the difference Fourier synthesis method; the F-based 2 The full-matrix least-squares method was used to refine the coordinates of all atoms and the anisotropic thermal parameters.

[0083] Powder X-ray diffraction was carried out on a Bruker D8 X-ray powder diffractometer from Bruker, Germany. The test conditions were a fixed target monochromatic light source Cu-Kα, a wavelength The voltage and current are 40 kV / 20 A, the slits DivSlit / RecSlit / SctSlit are 2.00 deg / 0.3 mm / 2.00 deg respectively, the scanning range is 5 to 70°, and the scanning step is 0.02°.

[0084] Among them, the single crystal X-ray diffraction results show that samples 2-1# to 2-8# have the same chemical formula and crystal structure, and the chemical formula is (D-C6H 10 N3O2)(H2PO2) belongs to the monoclinic system, the space group is P21, and the unit cell parameters are α=γ=90°, β=99.059~99.345°, Z=2.

[0085] Take sample 2-1# as a typical example, its crystal structure data is α=γ=90°,β=99.193(2)°,Z=2,the unit cell volume is Its crystal structure is Fig. 9 shown.

[0086] Take sample 2-1# as a typical example. Fig.10 As shown, according to the crystal structure analyzed by single crystal X-ray diffraction, the fitted X-ray diffraction pattern is consistent with the pattern obtained by X-ray diffraction test after sample 2-1# is ground into powder, and the peak position and peak intensity are consistent, indicating that the obtained samples are of high purity.

[0087] UV transmittance spectrum test

[0088] The UV transmission spectrum test of sample 2-1# was conducted on a Carry 5000 UV-Vis-NIR spectrophotometer from Agilent Technologies, USA. Fig.11 As shown by Fig.11It can be seen that the ultraviolet absorption cutoff edge of the compound is 234nm and the optical band gap is 5.30eV.

[0089] Infrared spectrum test

[0090] The infrared spectrum test of sample 2-1# was conducted on a Nicolet iS10 Fourier infrared spectrometer from Thermo Fisher Scientific Inc., USA. The results are as follows Fig.12 As shown by Fig.12 The group characteristic peaks of the compound can be seen, further confirming the accuracy of the crystal structure.

[0091] Thermogravimetric testing

[0092] The thermogravimetric test of sample 2-1# was conducted on a TGA / DSC1 / 1100SF thermogravimetric analyzer of Mettler-Toledo International Trading (Shanghai) Co., Ltd. The results are shown in Fig.13 As shown by Fig.13 It can be seen that the compound is stable up to 203 °C.

[0093] Frequency doubling test experiment and results

[0094] The frequency doubling test experiment of sample 2-1# is as follows: a Q-switched Nd:YAG solid laser is used to generate a laser with a wavelength of 1064nm as the fundamental frequency light to irradiate the tested crystal powder, a photomultiplier tube is used to detect the generated second harmonic, and an oscilloscope is used to display the harmonic intensity. The crystal sample and the standard sample KDP crystal are ground separately, and crystals of different particle sizes are sieved out with a standard sieve, and the particle size ranges are less than 50-74, 74-105, 105-150, 150-200, and 200-280μm, respectively. Observe the change trend of the frequency doubling signal with the particle size to determine whether it can achieve phase matching. Under the same test conditions, the second harmonic intensity generated by the sample and the reference crystal KDP under 1064nm wavelength laser irradiation is compared to obtain the relative size of the sample frequency doubling effect.

[0095] The test results showed that the compound (D-C6H 10 N3O2)(H2PO2) crystal has a large frequency doubling effect. Under 1064nm wavelength laser irradiation, the frequency doubling signal intensity is twice that of KDP crystal (such as Fig.14 ).like Fig.15 As shown, the crystal material can achieve phase matching in the 1064nm laser band.

[0096] Birefringence experiment and results

[0097] The birefringence test experiment of sample 2-1# is as follows:

[0098] (D-C6H 10The birefringence of N3O2)(H2PO2) was evaluated using a ZEISS Axio Scope 5 polarizing microscope equipped with a Berek compensator under a 546 nm light source. e -N o |×T=Δn×T to determine the birefringence, the optical path difference is R, the measured birefringence is Δn, and the crystal thickness is T.

[0099] The test results show that Fig.16 a, (D-C6H 10 N3O2)(H2PO2) is not extinguished. Fig.16 b, (L-C6H 10 N3O2)(H2PO2) is completely extinguished, and its optical path difference is 1.40μm. (D-C6H 10 The crystal thickness of N3O2)(H2PO2 is 24.138μm( Fig.16 c). According to the formula R = Δn × T, (D-C6H 10 The birefringence of N3O2)(H2PO2) is 0.058.

[0100] In the above embodiments, if there is no special description of materials or processing techniques, they are all conventional commercial products or conventional techniques in the art.

[0101] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A histidine hypophosphite inorganic-organic hybrid nonlinear optical crystal, characterized in that: Its chemical formula is A(H2PO2), where A is L-C6H 10 N3O2 or D-C6H 10 N3O2.

2. The histidine hypophosphite inorganic-organic hybrid nonlinear optical crystal according to claim 1, characterized in that: The optical crystal belongs to the monoclinic system, the space group is P21, and the unit cell parameters are α=γ=90°, β=99.0~99.4°, Z=2.

3. The histidine hypophosphite inorganic-organic hybrid nonlinear optical crystal according to claim 2, characterized in that: The chemical formula of the optical crystal is (L-C6H 10 N3O2)(H2PO2) belongs to the monoclinic system, the space group is P21, and the unit cell parameters are α=γ=90°, β=99.183~99.187°, Z=2; Or, the chemical formula of the optical crystal is (D-C6H 10 N3O2)(H2PO2) belongs to the monoclinic system, the space group is P21, and the unit cell parameters are α=γ=90°, β=99.191~99.195°, Z=2.

4. The method for preparing the histidine hypophosphite inorganic-organic hybrid nonlinear optical crystal according to any one of claims 1 to 3, characterized in that: The raw materials containing histidine source, hypophosphorous acid and water are mixed and placed in an open evaporation container for volatilization and crystallization to obtain the target product.

5. The method for preparing the histidine hypophosphite inorganic-organic hybrid nonlinear optical crystal according to claim 4, characterized in that: The histidine source is L-histidine or D-histidine.

6. The method for preparing the histidine hypophosphite inorganic-organic hybrid nonlinear optical crystal according to claim 4, characterized in that: The molar ratio of the histidine source, hypophosphorous acid and water is 5:5-10:500-1500.

7. The method for preparing the histidine hypophosphite inorganic-organic hybrid nonlinear optical crystal according to claim 4, characterized in that: The temperature of volatilization and crystallization is 15-45°C.

8. The method for preparing the histidine hypophosphite inorganic-organic hybrid nonlinear optical crystal according to claim 4, characterized in that: The time for volatilization and crystallization shall not be less than 14 days.

9. Use of the histidine hypophosphite inorganic-organic hybrid nonlinear optical crystal according to any one of claims 1 to 3 in a laser frequency converter.

10. The use of the histidine hypophosphite inorganic-organic hybrid nonlinear optical crystal according to claim 9, characterized in that: The laser frequency converter is used to output 532nm green light under 1064nm laser irradiation.

Citation Information

Patent Citations

  • Biocompatible MOF crystal material, composite material, preparation and application

    CN113234230A

  • Broad-band-gap fluorotungstic acid fluoroiodate mid-infrared nonlinear optical crystal material as well as preparation and application thereof

    CN115058776A

  • Mercury-based nitrate second-order nonlinear optical crystal material and preparation and application thereof

    CN116949575A